Pengaruh GUX dan Content Marketing terhadap Satisfaction dan Loyalty Pemain Game Mobile - Mikhael Candra Priadi; Erna Listiana; Bintoro Bagus Purmono; Ana Fitriana; Ahmadi (PT. PENERBIT TIGA MUTIARA, 2025)
The mobile gaming industry has evolved into a strategic sector within the global digital economy ecosystem, contributing significantly to the overall revenue of the gaming industry. A concrete manifestation of this dynamic is Honor of Kings (HoK), a 5v5 MOBA game developed by TiMi Studio Group, which has recorded over 100 million daily active players worldwide. The success of HoK is not solely determined by the quality of its game mechanics but also by its ability to deliver an immersive user experience and implement adaptive Content Marketing strategies. This study aims to empirically examine the influence of Game User Experience (GUX) and Content Marketing on Player Loyalty, with Satisfaction serving as a mediating variable. Employing a quantitative approach through Structural Equation Modeling (SEM), data were collected from active HoK players using a validated survey instrument. The results of the analysis indicate that both GUX and Content Marketing have a significant positive effect on Satisfaction, which, in turn, mediates their influence on Loyalty. The proposed mediation model successfully illustrates the affective role of Satisfaction as a key determinant in the formation of player Loyalty in digital contexts. These findings not only reinforce theoretical foundations in the domain of experience-based marketing but also offer practical insights for game developers and marketers in designing sustainable retention strategies through the optimization of gameplay experience and value-driven content delivery. Accordingly, this study presents a relevant conceptual framework for understanding the mechanisms of Loyalty formation within the competitive and dynamic mobile gaming industry.